Siloxane-modified bacterial cellulose as a promising platform for cell culture - Claro, Amanda Maria; Do Amaral, Nayara Cavichiolli; Colturato, Vitória Maria Medalha; Aleixo, Nadia Andrade; Paiva, Robert; Cruz, Sandra Andrea; Monteiro, Gustavo Claro; De Carvalho, Gustavo Senra Gonçalves; Nogueira, Flávia Aparecida Resende; Deffune, Elenice [UNESP]; Iemma, Mônica Rosas da Costa; Barud, Hernane da Silva (Springer Nature, 2022)
Cellulose is a versatile tunable material that finds application in the biomedical field as substrate for cell culture. However, few studies have been done to explore the use of bacterial cellulose (BC), a naturally occurring nanofibrillar material with distinct properties, as a platform to produce such device. In the present work, BC membranes have been functionalized with thiol functional group (SH) through silanization reaction with (3-mercaptopropyl)trimethoxysilane (MPTMS) under different conditions, in order to obtain a platform with improved cell adhesion. The efficiency of BC surface modification with MPTMS was evaluated by using acid and base catalyzed reactions, and two different drying methods: at room temperature of 28 °C and at 120 °C as curing temperature. The results of the set of analyses performed—ATR-FTIR, TGA, elemental analysis,13C NMR, contact angle and SEM—indicate that BC surface functionalization was efficient, regardless the drying process. The MPTMS-modified platforms exhibited sulfur content of 3–5 times higher than native BC. The performed biological assay with fibroblast GM07492 human cells revealed that adhesion of cells to the BC surface depends not only on the functional group present at the matrix but also on surface wettability. Graphical abstract: [Figure not available: see fulltext.]Schematic illustration of a siloxane-modified bacterial cellulose as platform for cell culture.
Keywords: Bacterial cellulose; Cell culture; Mercapto; Platform; Siloxane